2011
DOI: 10.1007/s10593-011-0804-2
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted N-allylation of uracil and thymine pyrimidine bases

Abstract: This work presents a new synthetic approach to N(1)-allylation of pyrimidine nucleobases with allyl bromide. The increased efficiency of the proposed method is based on two specific elements: (a) the nucleoside N-deprotonation is carried out in a homogeneous system by using sodium methylsulfinylmethylide in DMSO; (b) the allylation reaction is microwave-assisted. This method ensures high yields (87-88%) of the monoallylated products and short reaction time (1.5 h as compared to tens of hours for classical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The N-allylation of T was also described involving two reaction steps, first heating at 65°C for 30 min followed by MW irradiation for 2 min. [29] In this work, the treatment of A, T, C and G with allyl bromide 22, in basic conditions under MW, led to the desired N-allylic pyrimidine and purine derivatives 18-21 in low to moderate yields (16-43 %, Table 3) in a shorter reaction time.…”
Section: Functionalization Of Nucleobases Via N-allylation and N-propargylation Reactionsmentioning
confidence: 75%
See 1 more Smart Citation
“…The N-allylation of T was also described involving two reaction steps, first heating at 65°C for 30 min followed by MW irradiation for 2 min. [29] In this work, the treatment of A, T, C and G with allyl bromide 22, in basic conditions under MW, led to the desired N-allylic pyrimidine and purine derivatives 18-21 in low to moderate yields (16-43 %, Table 3) in a shorter reaction time.…”
Section: Functionalization Of Nucleobases Via N-allylation and N-propargylation Reactionsmentioning
confidence: 75%
“…Recently, it has been shown that primary alcohols are appropriate candidates to react with nucleobases, leading to N-alkyl derivatives in good yield and with low toxicity. [21] The chemical modification of nucleobases with either terminal alkyne, [22][23][24] acrylate, [25][26][27] allyl, [28,29] acrylonitrile [26,[30][31][32] or thiol [33] functional groups at the secondary amine has been explored in the last decades and, in most of the cases, A and T have been at the limelight. From the chemical functionalization standpoint, the major bottlenecks associated to these functionalization strategies include the development of efficient synthetic methodologies for the successful introduction of reactive terminals at C and G, as well as simple and direct methods for the regioselective functionalization of the DNA nucleobases, aiming to preserve their hydrogen bonding capabilities.…”
Section: Introductionmentioning
confidence: 99%